Psychological Treatments for Hypochondriasis: A Narrative Review - K. Bouman, Theo (Current Psychiatry Reviews, 2014)
This paper presents a narrative review of psychological treatments for hypochondriasis and health anxiety. An extensive literature search encompassing publications in the English language yields over 40 case reports and systematic studies on mainly cognitive and behavioral interventions. After a brief introduction of the types of intervention, a summary of recent studies is given, and their methodological and clinical status are being discussed. It is concluded that there is a general evidence for psychological treatments (in particular cognitive-behavioral interventions) to be effective in reducing hypochondriacal symptoms. However, since most studies possess methodological flaws, their results should be interpreted with care.
Keywords: Hypochondriasis